Menimbang Akuntansi Konvensional dan Syariah: Antara Logika Bisnis dan Nilai Ilahiah - Nesa Usdayanti; Nur Isma Arham; Masyhuri Masyhuri (Journal of Economics, Management, and Accounting, 2025)
This study aims to explore the philosophical and practical differences between conventional accounting and Islamic accounting in contemporary financial reporting. While conventional accounting places greater emphasis on economic efficiency and profitability, Islamic accounting highlights justice, trustworthiness, and obligations aligned with spiritual values. This research employs a qualitative descriptive approach through a literature review of relevant journals, as well as IFRS, PSAK, and AAOIFI standards. The findings indicate that conventional accounting seeks to provide information to support investment decisions, whereas Islamic accounting incorporates social and spiritual dimensions through reports such as zakat and Sharia compliance disclosures. The conclusion of this study suggests that by implementing Sharia standards, supervision by the Sharia Supervisory Board (DPS), and transparent reporting, both business value and spiritual principles can be harmonized.